The Effect of Washing Eggs of Patin Catfish (P. hypophthalmus) using Different Solutions on Adhesion, Fertilization Rate, Hatching Rate andSurvival Rate of Larvae - Riana Meynarti Situmorang; Nuraini Nuraini; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThis research was conducted in August-September 2020 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine, Universitas Riau, Pekanbaru. This research aims to determine the effect of different washing solutions (milk, urea, formalin) on eggs adhesive, fertilization rate, hatching, and the survival of Patin catfish (P. hypophthalmus) larvae. This experimental research used a completely randomized design with a factorial pattern (CRD) with 1 factor, 4 levels of treatment, and 3 replications. The treatment levels covered PA: No washing (Control), PS: 14 grams of powdered milk + 1 gram of NaCl/L of water (20 minutes), PU: 4 grams of urea + 4 grams of NaCl/L of water (5 minutes), PF: 0.4 mg formalin/L of water (10 minutes). The washing was performed on 1 gram of eggs or with a density of ± 1153 eggs in each treatment which was then incubated in a container in an egg hatching funnel. The best washing solution for washing eggs contained 14 grams of powdered milk + 1 gram of NaCl resulting in 100% of eggs that do not stick together (non-adhesive) and the fertilization rate reached 76.52% with the hatching rate of 76.98% and larval survival (SR 5 days) of 87.11%.Keywords: Milk solution, urea, formalin, adhesiveness, fertilization, hatching, survival